Palladium-Catalyzed Cross-Coupling of Arenediazonium Salts with Organoindium or Organobismuth Reagents - Riemer, Nastja; Coswig, Christin; Shipman, Mike; Schmidt, Bernd (Synlett, 2018)
Arylindium and isolated triarylbismuth compounds generated in situ react as nucleophiles with arenediazonium salts in palladium-catalyzed cross-coupling reactions to give substituted biphenyls.
Keywords: palladium catalysis; cross-coupling; arenediazonium salts; organobismuth compounds; organoindium compounds